Firn density and ice content at two sites along the west Expéditions Glaciologiques Internationales au Groenland (EGIG) line, Greenland, 2024 ... - Harper, Joel; Humphrey, Neil (NSF Arctic Data Center, 2024)
This archive contains data collected at two sites located along the lower elevation portion of the Expéditions Glaciologiques Internationales au Groenland (EGIG) line, western Greenland Ice Sheet. The data include the physical stratigraphy measured in firn cores extending to depths of 10 and 25 meters (m) with measurements of firn density and refrozen ice content. The data were collected as part of an Arctic Observing Network (AON) project funded by the U.S. National Science Foundation. The study sites are located in the Greenland Ice Sheet’s Percolation Zone, the outer flanks of the accumulation zone that experiences surface melt during the summer period. Data collection for this AON project began in 2022 and is expected to continue through 2025. This dataset is associated with numerous other datasets containing observations collected at sites along the EGIG line, including physical stratigraphy and density measured in ice cores and firn temperature time series measured in core holes. ...